Control of Phytophthora palmivora on Orchids with Some New Systemic and Standard Fungicides - Lim , Tong Kwee; Lam, Nio Huat (1983)
Three new systemic fungicides viz. Aliette (efosite-Al), Ridomil (metalaxyl) and Ridomil MZ (metalaxyl plus mancozeb) were screened against two standard fungicides viz. Terrazole (etridiazole) and Difolatan (captafol) for prophylactic and therapeutic efficacy against Phytophthora palmivora on orchids. Terminal shoots of Aranda Christine hybrids were effectively protected from Phytophthora infection when sprayed with metalaxyl at 0.05% a.i., metalaxyl-mancozeb mixture at 0.15% a.i. and captafol at 0.2% a.i. three days before artificial inoculation. Etridiazole and efosite-Al, both at 0.1%a.i. did not give adequate protection. Metalaxyl (0.05% a.i.) and its mixture with mancozeb (0.15% a.i.) retarded significantly disease development by Phytophthora when used as a curative spray. Etridiazole (0.1% a.i.) and efosite-Al (0.1% a.i.) gave moderate therapeutic control while captafol gave no therapeutic control. No phytoxicity was observed with Ridomil MZ, Terrazole and Aliette up to concentrations of 0.5% a.i., 0.4% a.i. and 0.8% a.i. respectively. The Ridomil products, Aliette and Terrazole exhibited similar rates of inhibition of linear extension of P. palmivora but differed in the degree of in vitro fungitoxicity. The Ridomil products and Terrazole had EDso values of less than 1 Ilg/ml while Difolatan was relatively less toxic (ED so 19.9 Ill/l).